A heuristic for a special kind of multi-type component assignment problem. Issue 2 (January 2021) - Shi, Y; Guan, Z; Qiu, S
Abstract: The multi-type component assignment problem (MCAP) is to assign more than one type of components to positions in the system to maximize system reliability. This paper proposes a two-stage Birnbaum importance-based local search heuristic to address a special kind of MCAP where positions in the system can accept up to two types of components. To evaluate the performance of the heuristic, comprehensive simulation experiments are conducted across different types of systems. The results demonstrate the heuristic's efficiency and applicability. It shows that the Birnbaum importance is also promising in solving MCAPs.